Teledermatology: idea, benefits and risks of modern age – a systematic review based on melanoma - Pala, Paulina; Bergler-Czop, Beata S.; Gwiżdż, Jakub (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2020)
Telemedicine may be described as a modern technology supporting health care at a distance. Dermatology, as a visually-dependent specialty, is particularly suited for this kind of the health care model. This has been proven in a number of recent studies, which emphasized feasibility and reliability of teledermatology. Many patients in the world still do not have access to appropriate dermatological care, while skin cancers morbidity is on an upward trend. Technological development has enabled clinicians to care for diverse patient populations in need of skin expertise without increasing their overhead costs. Teledermatology has been used for various purposes: health care workers can use this technology to provide clinical services to patients, to monitor patient health, to consult with other health care providers and to provide patients with access to educational resources. It seems that teledermatology might be the answer to numerous issues concerning diagnosing, screening and managing cancers as well as pigmented skin lesions.